2023
DOI: 10.1177/00045632231154731
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference intervals for plasma metanephrines in seated position measured by LC-MS/MS and assessment of diagnostic performance in pheochromocytoma/paraganglioma

Abstract: Background: The use of supine reference intervals instead of the corresponding seated reference intervals for seated plasma-free metanephrines (MNs) in pheochromocytoma /paraganglioma (PPGL) screening has been controversial in recent years. Each clinical laboratory should choose the optimal sampling posture and diagnostic strategy according to local conditions. Methods: The reference population consisted of 736 cases aged 14 to 92 years old and the validation population consisted of 1068 patients aged 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…There has been some debate over whether supine sampling is necessary in all patients under investigation for PPGL [ 72 , 73 ], as although this is ideal, some diagnostic centres may find it difficult to provide the resources necessary for supine sampling in all patients. Some researchers have published data suggesting that seated sampling offers a high degree of diagnostic sensitivity and so have argued that seated sampling is acceptable [ 74 , 75 ]. A large study of the diagnostic performance of plasma and urine metanephrines in different patient groups by Eisenhofer at al [ 44 ] found that false negatives were more likely in patients undergoing surveillance due to an increased risk of PPGL (due to a genetic predisposition or history of treated PPGL) as minor elevations in plasma and urine metanephrines were more common (these patients are more likely to be harbouring small, pre-symptomatic PPGL).…”
Section: Pre-analytical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some debate over whether supine sampling is necessary in all patients under investigation for PPGL [ 72 , 73 ], as although this is ideal, some diagnostic centres may find it difficult to provide the resources necessary for supine sampling in all patients. Some researchers have published data suggesting that seated sampling offers a high degree of diagnostic sensitivity and so have argued that seated sampling is acceptable [ 74 , 75 ]. A large study of the diagnostic performance of plasma and urine metanephrines in different patient groups by Eisenhofer at al [ 44 ] found that false negatives were more likely in patients undergoing surveillance due to an increased risk of PPGL (due to a genetic predisposition or history of treated PPGL) as minor elevations in plasma and urine metanephrines were more common (these patients are more likely to be harbouring small, pre-symptomatic PPGL).…”
Section: Pre-analytical Considerationsmentioning
confidence: 99%
“…Posture during sample collection for the reference population also has a significant effect on plasma metanephrine reference ranges [ 56 ], with seated healthy individuals having significantly higher normetanephrine than supine individuals. The application of higher, seated reference ranges or lower supine ranges may have a significant effect on diagnostic sensitivity and specificity, although this will also depend on the posture used for collection of samples in clinical practice [ 56 , 74 , 75 ]. For example, applying lower supine ranges while collecting samples in a seated position will likely lead to a high false-positive rate, while applying higher seated ranges while collecting samples in a supine posture may lead to impaired diagnostic sensitivity [ 56 ].…”
Section: Post-analytical Considerationsmentioning
confidence: 99%